(untitled) (Altre Modernità, 2011)
Starting from a due reflection on Miguel Barnet’s Cimarrón as the first experiment on a testimony-novel – and considering the problems and contradictions of a cultural and political operation in which the witness-informant’s voice risks being overcome or at least misinterpreted by the author-transcriber – this paper goes on to consider the evolution of the testimony genre in 1990s Cuba, where women of African descent often intervened by speaking or writing, and managed to impose their views autonomously.